Narasi Penciptaan dalam Kejadian 1–2 dan Relevansinya Bagi Martabat Manusia - Emilianus Rango; Leonardo Kristian Magung; Edwar Firmanto Meo Pau (CV. ALIM'SPUBLISHING, 2026)
The creation narrative in Genesis 1–2 serves as an essential theological foundation for understanding the origin of the world and the nature of humanity. This text not only describes God’s creative acts but also affirms the unique dignity of human beings. This study aims to examine the meaning of the creation narrative in Genesis 1–2 and its relevance to the concept of human dignity in the modern era. The method employed is a literature study using exegetical and theological approaches, through analysis of biblical texts and relevant scholarly sources. The findings indicate that Genesis 1 emphasizes order, the goodness of creation, and the creation of humans in the image and likeness of God (imago Dei), while Genesis 2 highlights the relational and existential dimensions of humanity, including relationships with God, others, and nature. The concept of imago Dei affirms that humans possess intrinsic value, freedom, reason, and moral responsibility. In a contemporary context, this narrative remains relevant as an ethical foundation to reject violations of human dignity such as discrimination, violence, and exploitation, while also encouraging ecological awareness and responsibility toward the environment. Therefore, the creation narrative holds not only theological significance but also contributes meaningfully to the development of humane, dignified, and sustainable values.